The effect of an imagery training intervention on self-confidence, anxiety and performance in acrobatic gymnastics - A pilot study - Marshall, E. A.; Gibson, A.-M. (Journal of Imagery Research in Sport and Physical Activity, 2017)
Acrobatic gymnastics is a unique sport due to the different mixes of gender, age and number of gymnasts working in each partnership, however psychological skills training within this domain is currently unknown. The aim of this study was to examine the effect of an imagery training intervention on acrobatic performance, self-confidence and anxiety in acrobatic gymnastics. Participants (n=19) completed the Sport Imagery Questionnaire and the Competitive State Anxiety Inventory 2 prior to performing their competition routine. They were then randomly assigned to a 4 week imagery training intervention (n=11) or control group (n=8). Repeated measures ANOVAs were used to examine changes in acrobatic performance, levels of self-confidence and anxiety. The imagery intervention significantly increased acrobats` self-confidence, however imagery did not significantly reduce anxiety or improve acrobatic performance. Future research should consider adopting a longer intervention period to elicit a reduction in anxiety levels and an enhancement of acrobatic performance.